STUDI BAKTERI HETEROTROPIK SEBAGAI INDIKATOR PENCEMARAN DI PERAIRAN SUNGAI BRANTAS - Imamuddin, Hartati (Jurnal Hidrosfir Indonesia, 2010)
The experiment was carried out to study the level of pollution of organic substances entering Brantas River. The water samples were taken twice in a year from 5 stations(Juni dan Agustus 2006..). The number of bacteria was counted by plate count technique. Results showed that 17 species of heterotrophic bascteria were found in the first survey, and 16 species in the second survey, the number of species in first survey ang second survey is almost the same but different from species dominant because the water quqlity is also slightly change ( tables 4 and 7. Bacterial population was composed of various species and varied in each stasiun.The various of the species occuredbecause every species has different activity for degrading the types of waste. Pollution level is inversely correlated with number of heterotrophic bacteria.